Theoretical prevision for the low-energy 3S1-3D1 mixing parameters - Adhikari, Sadhan K. [UNESP]; De Araujo, Carlos F. [UNESP]; Frederico, T. (American Physical Soc, 1994)
Using a recent shape-independent approximation for the 3S1-3D1 mixing parameter, theoretical prevision for the low-energy mixing parameters is made. The present prevision is consistent with the deuteron binding energy, its asymptotic D-state to S-state ratio, ηd, the triplet-scattering length, and the meson exchange tail of the tensor nucleon-nucleon potential. The theoretical prevision up to an incident laboratory energy of 25 MeV is consistent with the recent multi-energy determination of mixing parameters, but is much higher than many single-energy determinations of the same. The low single-energy values of the mixing parameter could be reproduced by meson-theoretical potentials only with a substantially reduced ηd. © 1994 The American Physical Society.